Characterisation Of Fungi Associated With Diseased Sansevieria Trifasciata In Malaysia - Kee, Yee Jia (2019)
Sansevieria trifasciata is a popular ornamental plant that can be widely found in Malaysia. It is an easy to be taken care plant as it is tolerant of low light intensity and water supply. However, S. trifasciata is susceptible to various diseases, particularly those caused by fungi. The present study was conducted to isolate, identify and characterise the fungi associated with diseased S. trifasciata in Malaysia. Pathogenicity test was then conducted to confirm the pathogenicity of the isolates. A total of 100 fungal isolates were recovered from diseased S. trifasciata from Penang, Perak, Kedah, Kelantan, Pahang, Kuala Lumpur, Selangor, Melaka, Negeri Sembilan, Johor, Sabah and Sarawak. Based on morphological and molecular characteristics (DNA sequences), the isolates were identified as Collctotrichum sansevieriae (44 isolates), C. truncatum (one isolate), C. endophytica (one isolate), C. tropicale (five isolates), C. fructicola (one isolate), C. alienum (six isolates), Lasiodiplodia brasiliense (one isolate), L. hormozganensis (eight isolates), L. iraniensis (one isolate), L. pseudotheobromae (three isolates), L. theobromae (two isolates), Ncoscytalidium dimidiatum (eight isolates), Fusarium oxysporum (11 isolates), F. solani (two isolates), F. brachygibbosum (one isolate), Stemphylium lycopersici (two isolates), Curvularia eragrostidis (one isolate), Cu. geniculata (one isolate) and Diaporthe tectonae (one isolate). Identification of the Colletotrichum isolates were confirmed via phylogenetic analysis of combined internal transcribed spacer (ITS), p-tubulin and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) sequences.